a study of the effect of irrigation water quality ( fresh and water ) on some soil physical and chemical properties and the growth of paulonia trees in homs region (Journal of Hama University, 2024)
Abstract A field experiment was carried out during the 2019-2020 and 2020-2021 agricultural seasons In the village of Nasiriyah, which is located on the southwestern side of the Al-Qusayr region, about 35 km from the Homs city. The aim was to study the effect of using wastewater on some chemical properties of soil and its content of some heavy metals.Three types of irrigation water were used in the experiment: fresh water (F), wastewater (W), and fresh and wastewater (F1W1, alternating irrigation). Soil samples for irrigation treatments were collected from depths of 0-15 and 15-30 cm during the two experimental seasons, and some soil properties were determined: electrical conductivity, pH, total carbonate, active lime, organic matter, and the concentration of phosphorus, potassium, and heavy metals (lead, cadmium, and nickel).The results showed that there were no significant differences in the values of soil pH, total carbonate, and effective lime between the three treatments, while the use of wastewater led to a significant increase in the electrical conductivity of the soil and organic matter compared with soil irrigated with fresh water and irrigated alternately with fresh and wastewater at depths of 0-15 and 15-30 cm. The use of wastewater also led to a higher concentration of both phosphorus and potassium in the soil compared to the use of fresh water.The results also showed that using wastewater in irrigation led to a significant increase in the soil content of heavy metals (lead, nickel, and cadmium) compared to using fresh water only or using fresh and wastewater alternately, but it did not exceed the maximum limits of the Syrian standard specifications for soil, so it can be considered this water is suitable for agricultural uses.